2020
DOI: 10.1038/s41467-020-20032-3
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen-deuterium exchange mass spectrometry captures distinct dynamics upon substrate and inhibitor binding to a transporter

Abstract: Proton-coupled transporters use transmembrane proton gradients to power active transport of nutrients inside the cell. High-resolution structures often fail to capture the coupling between proton and ligand binding, and conformational changes associated with transport. We combine HDX-MS with mutagenesis and MD simulations to dissect the molecular mechanism of the prototypical transporter XylE. We show that protonation of a conserved aspartate triggers conformational transition from outward-facing to inward-fac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 47 publications
(67 reference statements)
3
34
0
Order By: Relevance
“…Given its salt bridge interaction with Arg133, the Asp27 must be in a deprotonated state, consistent with MD simulations. 272 Yet, the fact that the substrate can bind in this conformation implies that protonation of Asp27 is not a prerequisite for substrate binding in XylE, unlike in LacY and other H + -coupled symporters, where protonation of a key residue in the substrate binding site is required in the wild-type situation. 90 In contrast to LacY, the transporter XylE, like many of the monosaccharide sugar porters, lacks an ionizable residue in the sugar binding pocket ( Figure 10 b).…”
Section: The Alternating-access Mechanism Of Glucose (Glut) Transportmentioning
confidence: 99%
See 2 more Smart Citations
“…Given its salt bridge interaction with Arg133, the Asp27 must be in a deprotonated state, consistent with MD simulations. 272 Yet, the fact that the substrate can bind in this conformation implies that protonation of Asp27 is not a prerequisite for substrate binding in XylE, unlike in LacY and other H + -coupled symporters, where protonation of a key residue in the substrate binding site is required in the wild-type situation. 90 In contrast to LacY, the transporter XylE, like many of the monosaccharide sugar porters, lacks an ionizable residue in the sugar binding pocket ( Figure 10 b).…”
Section: The Alternating-access Mechanism Of Glucose (Glut) Transportmentioning
confidence: 99%
“…Consistent with this rationale, recent HDX-MS and MD simulations of XylE concluded that (i) when Asp27 is negatively charged, the binding of d -xylose stabilizes the outward-facing state and is stably bound, (ii) upon Asp27 protonation, TM1 become more dynamic and increased water solvation that leads to d -xylose adopting multiple states, and (iii) that Asp27 protonation is a critical switch for conformational transition into the inward-facing state. 272 …”
Section: The Alternating-access Mechanism Of Glucose (Glut) Transportmentioning
confidence: 99%
See 1 more Smart Citation
“…The structure-function relationship of amphiphilic polymers and their thermal stabilization effect was investigated. All-atom classical molecular dynamics (MD) simulations of complexes (BSA with and without PEG or/and C 18 fragment, respectively) were performed in Amber18 package to study the stability of protein backbone under the different temperatures ( Bondanza et al., 2020 ; Jia et al., 2020 ). Final 100 ns trajectories were used for further analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Unlike higher resolution approaches, HDX-MS offers the advantage of obtaining dynamic structural information for samples that presents heterogeneous and/or flexible areas. It was successfully applied to characterize the dynamics and interactions of membrane transporters and even GPCRs (Du et al, 2019;Fiorentino et al, 2020;Jia et al, 2020;Möller et al, 2019;Reading et al, 2020;Zhang et al, 2010). HDX-MS optimization for ACKR1 allowed the identification of 77 peptides covering 70.1 % of WT ACKR1, with 3.41 peptide redundancy (Fig.…”
Section: Conformational Changes Of Ackr1 Upon Binding To Leukotoxins mentioning
confidence: 99%